2014
DOI: 10.1111/ejed.12098
|View full text |Cite
|
Sign up to set email alerts
|

Student Guidance and Attention to Diversity in the Processes of Quality Assurance in Higher Education

Abstract: The main objective of this article is to analyse the importance given to student guidance and diversity in the standards and criteria used in the quality accreditation and evaluation processes in Europe and the US. Agencies selected in this study are the members of ENQA (European Association for Quality Assurance in Higher Education), EQAR (European Quality Assurance Register for Higher Education) and regional and programme accrediting organisations in the US that are recognised by the Council for Higher Educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 6 publications
0
15
0
3
Order By: Relevance
“…The research conducted by Ferrão and Almeida (2018) showed that the university entrance score is the best predictor of the GPA obtained at the end of the first year at the University of Minho. The authors refer that the student's prior knowledge and preparation are essential to his/her success in higher education, confirming the international literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research conducted by Ferrão and Almeida (2018) showed that the university entrance score is the best predictor of the GPA obtained at the end of the first year at the University of Minho. The authors refer that the student's prior knowledge and preparation are essential to his/her success in higher education, confirming the international literature.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, dropout rates have increased in Portugal, and institutions have been questioned about their policies to support student retention (DIAS et al, 2011;VIDAL;VIEIRA, 2014), in particular with regard to the goals of the Europe 2020 strategy (EUROPEAN COMMISSION, 2013) targeting 40% of young adults with a higher education diploma.…”
Section: Introductionmentioning
confidence: 99%
“…There is a broad consensus on the need for universities to promote students' success, since many do not achieve their goals or fully realise their potential during their university experience, thus wasting talent and human potential. The rates of failure and abandonment have increased in recent years in Portugal, leading to questions regarding how institutions can support student retention (Dias et al 2011;Ferreira, Vidal, and Vieira 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of Finnish higher education, the term guidance (ohjaus) refers to a variety of student support and advice services, such as activities related to study planning, tutoring, mentoring and counselling, thesis supervision, internship guidance, career planning, and facilitation of learning (Moitus and Vuorinen 2003). In international discussions, these aspects often fall under the concept of academic student support, and the services provided for students' welfare and academic success are referred to as student services or student support (Dhillon, McGowan, and Wang 2008;Ferreira, Vidal, and Vieira 2014;Morgan 2012;Sajiené and Tamuliené 2012). Thus, student support refers to a system of services that aims at fulfilling students' academic and nonacademic (emotional and social) needs (Sajiené and Tamuliené 2012, 121;Dužević and Čhe Časni 2015).…”
Section: Various Forms Of Guidancementioning
confidence: 99%